Comparison of different substrates for growth behaviour and yield potential of oyster mushroom P. djamor (Rumph.) Boedijn - CHANDRA, RAM; Saumya (Mushroom Research, 2021)
The present study was undertaken to observe the different agricultural wastes for growth behavior and yield potential of oyster mushroom (Pleurotus djamor) with a view to help the mushroom growers in selection of substrates for obtaining better growth and yield. Experimental findings showed that maximum total yield was obtained from wheat straw mushroom bag (941.13gm/bag) followed by mixture substrate of wheat straw with paddy straw (1:1), wheat straw with saw dust (1:1), wheat straw with paddy straw and tamarind leaves (1:1:1) and wheat straw with paddy straw and Bermuda grass (1:1:1) having 811.78g, 628.33g, 533.15g and 473.90g yield respectively. Spawn run period, weight of fruiting body was also found better in wheat straw substrate. So, the best performing substrate was wheat straw for yield and yield contributing parameters of oyster mushroom. This investigation will help to mushroom growers for selection of suitable substrate for cultivation of oyster mushroom (Pleurotus djamor).